Government contracts law and procedure - Agarwal, Vinod K. 1940- (Delhi, India Eastern Book Corp., 1984)
In the Indian context.
Based on the authors thesis (Ph. D.--University of Bombay, 1970)
Keywords: Public contracts -- India